SIKAP BAHASA MAHASISWA TERHADAP BAHASA INDONESIA DI TENGAH PENGARUH LINGKUNGAN SOSIAL, BAHASA GAUL, DAN MEDIA SOSIAL - Mara Untung Ritonga; Halimatussadi'yah Dalimunthe; Mutia Patmasari Batubara; Regina Tesalonika Silaban (STKIP Subang, 2026)
Changes in students’ interaction and communication patterns in the digital era cannot be separated from the influence of social media, technological advancements, and the diversity of language varieties used in daily life. These factors have affected the use of the Indonesian language in both academic settings and casual conversations. This study aims to describe students’ attitudes toward the Indonesian language and the factors influencing them, with a particular focus on the role of the social environment, non-standard language use, and online platforms. Data were collected through an online questionnaire distributed via Google Forms and completed by 22 university students. The results indicate that the majority of respondents hold positive attitudes toward the Indonesian language in educational contexts: 86.4% strongly agreed that Indonesian should be used during presentations, and all participants agreed that standard Indonesian is mandatory for academic assignments. In contrast, 95.5% reported using informal language more frequently in daily conversations, while 68.2% often mixed Indonesian and English in their communication. The findings also reveal that social media is the most influential factor shaping students’ language habits. In conclusion, students demonstrate an understanding of the functions of the Indonesian language and are able to adjust their language varieties according to different communicative situations.